Diversity and Morphometric Characteristics of Freshwater Fish in the Air Manna River, Pino District, South Bengkulu Regency - Pariyanto, Pariyanto; Syahfitri, Jayanti; Rahmadania, Lidya (Techno: Jurnal Penelitian, 2021)
This study aims to determine the diversity and morphometric characteristics of freshwater fish in the Air Manna river, Pino District, South Bengkulu regency. Determination of the location was done by using the purposive sampling method. Sampling was done by dividing the station on river characteristics which consists of three locations, namely station A with calm water characteristics, station B with slow-flowing water characteristics, and station C with fast water characteristics. 9 species of fish were included in 8 families, namely Anguillidae (Anguila bicolor), Bagridae (Mystus mierus), Cyprinidae (Osteochilus vittatus), (Tor dourenensis), Gobiinae (Sicyopteruscynocephalus), Clariidae (Clarias batrachus), Channidae (Channa striata), Cichlidae (Oreochromis Oslogosterm tricida) (hops) ). Measurement of morphometric characteristics of Osteochilusvittatus (Nilem) and Oreochromisniloticus (Tilapia) fish was carried out to see the ratio of the character ratio PT: TB, PT: PK. and PS: PSE at stations A, B, and C by measuring fish body part, total length (PT), body height (TB), head length (PK), standard length (PS), and tail fin length (PSE). The results show that the diversity of fish found in three stations has differences in fish diversity at station A with a diversity index of 0.080, station B with a diversity index of 0.856.